2019
DOI: 10.1096/fj.201801519rr
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 phosphorylation at Ser897 by the Cdk1/MEK/ ERK/RSK pathway regulates M‐phase progressionviamaintenance of cortical rigidity

Abstract: Successful cell division is accomplished by the proper formation of the mitotic spindle. Here, we show that EphA2 knockdown causes mitotic errors, including a delay in M‐phase progression, asymmetric spindle positioning, multipolar spindles, and cell blebs. It has been known that EphA2 is phosphorylated at Tyr588, which is triggered by the ligand binding, and at Ser897 downstream of growth factor signaling. Upon mitotic entry, EphA2 is phosphorylated at Ser897, accompanied by a reduction in Tyr588 phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…We performed GO analysis of downstream pathways and GSEA of these differentially expressed genes and found that ABCC5 highly expressed in prostate cancer may act through multiple tumor-related pathways, including the PI3K-Akt and MAPK/ERK signaling pathway and E2F target genes (Figure 4A-B). Previous studies have reported a regulatory relationship between the PI3K-Akt and MAPK/ERK signaling pathways and CDK1 [28,29]. Immediately thereafter, we analyzed transcriptomic data from prostate cancer patients using the WGCNA approach and found that the pink module was highly correlated with ABCC5 expression levels (R = 0.39, p = 4e-19) (Figure 4C-E).…”
Section: Downstream Pathway Prediction Of Abcc5 Combined With Bioinformatics Analysismentioning
confidence: 83%
“…We performed GO analysis of downstream pathways and GSEA of these differentially expressed genes and found that ABCC5 highly expressed in prostate cancer may act through multiple tumor-related pathways, including the PI3K-Akt and MAPK/ERK signaling pathway and E2F target genes (Figure 4A-B). Previous studies have reported a regulatory relationship between the PI3K-Akt and MAPK/ERK signaling pathways and CDK1 [28,29]. Immediately thereafter, we analyzed transcriptomic data from prostate cancer patients using the WGCNA approach and found that the pink module was highly correlated with ABCC5 expression levels (R = 0.39, p = 4e-19) (Figure 4C-E).…”
Section: Downstream Pathway Prediction Of Abcc5 Combined With Bioinformatics Analysismentioning
confidence: 83%
“…S9B). The association best known to be important for EphA2 non-canonical signaling is that involving the RHOG guanine nucleotide exchange factor Ephexin4 (gene name ARHGEF16), which leads to downstream activation of the RHOG-RAC and PI3K-AKT axes to promote cell migration, survival and proliferation [60][61][62] . Ephexin4 has been reported to interact with the EphA2 kinase domain in co-immunoprecipitation experiments 60,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Activated RAF proteins then amplify the signal by phosphorylating multiple MAPK proteins (including Mek1/2), which are themselves kinases and go on to phosphorylate multiple ERK-like proteins [15]. Many of the substrates are transcription factors in the nucleus [16], but some are powerful signaling molecules, such as ribosomal S6 kinases (RSKs) [16]. There are numerous MAPK family members that signal using a similar template to that of ERK1/2, including the more characterized p38, JNK, and ERK5 signals.…”
Section: Figurementioning
confidence: 99%
“…The cell cycle is also regulated by a large number of kinases, and cell division is highly regulated during erythropoiesis [16][17][18]. There is evidence that cell cycle progression and differentiation is uncoupled in DBA and is yet another area that deregulated kinases may be impacting erythropoiesis [19].…”
Section: Introductionmentioning
confidence: 99%